KEBERLANJUTAN KESEJAHTERAAN RAKYAT INDONESIA : MENYONGSONG PENCAPAIAN MILLENIUM DEVELOPMENT GOALS (MDGs) TAHUN 2015: MDGs, Indonesia, poverty - admin, admin (JAMAK, 2014)
Millenium Development Goals (MDGs) are eight goals of development in response to global problems, to be achieved by 20 15.We recognize that the MDGs are quantifiable targets global poverty and other dimensions of poverty, such as hunger, disease, basic infrastructure (water supply, housing / residential) gender equality, education and the environment.Deadline set by the UN Millennium Declaration by 2015 requires the commitment of all stak eholders of the Indonesian nation.Meanwhile, the problem of the global financial crisis, natural disasters, climate change, and public official corruption and accountability are all factor s that need consideration as well as other issues related to the development gap between regions in different parts of Indonesia.